Detection of hepatitis B surface antigen in aqueous humor - (:unkn) unknown (My University, 1990)
Abstract We detected hepatitis B surface antigen (HBsAg) in tears and aqueous humor of 18 patients who upon preliminary examination were seropositive for HBsAg and were scheduled to undergo cataract extractions. HBsAg remained detectable in the serum of 10 of these patients on the day of operation, and of these, 7 were found to have detectable levels of HBsAg in their tears and aqueous humor. Based on our findings, we caution ophthalmologists to take all the necessary precautions in both surgical and nonsurgical treatment of patients at high risk for hepatitis B infection. 1990 Institution Acta Ophthalmologica Scandinavica
Keywords: aqueous humor; hepatitis B surface antigen (HBsAg); hepatitis B virus; tears